Vegetation and climate from Late Quaternary Thimi Formation (Phaidhoka Section), Bhaktapur, Nepal (Journal of Nepal Geological Society, 2015)
The Thimi Formation is fluvio-deltaic deposit that constitutes the uppermost part of the sedimentary sequence in the Kathmandu Basin, and is featured by carbonaceous and diatomaceous clay, silty clay, silt, fine to medium grained sand beds, and thin to medium lignite beds. The Phaidhoka Section is located on the way to Nala from Chyamasingh, and is one of the major exposures of the Thimi Formation. Forty four samples were collected from 25 m thick surface exposure for palynological study. The study revealed the dominance of gymnosperm over the angiosperm and herbaceous members. The pollen diagram suggested Pinus, Picea and Quercus as the most dominant trees whereas Poaceae is other dominant among the grasses. Three major pollen assemblage zones were marked in the Thimi Formation. Zone P-I indicated warm temperate climate, whereas zone P-II and P-III indicated cold temperate climate. Molluscan operculum in the upper part indicated shallow water condition. The Bovid molars, limb and pelvic bones from the middle part of the section confirm the early findings of molar bones in this area.